A Comparative study of Vamandhauti (kunjal kriya) and Bilvadipanchmula kwath with Madhu in the Management of Sthaulya (Obesity) - Singh, Ratan; Gupta, Piyush; Lakkundi, Shridhar S (International Research Journal of Ayurveda & Yoga, 2022)
In Present era every person is running after life,s goal. Hence does not have time to think and act for the healthy life and also not able to follow the proper Dincharya, Ratricharya, Ritucharya and rules for healthy living as per Ayurveda and other life sciences so that obesity has taken place as an major problem in majority of peoples. Sthaulya (Obesity) is such a disease ,which provides the platfrom for so many disease and complication like hypertension, Congenital heart disease, diabetes mellitus, impotency as well as psychological disorders like stress, anxiety, depression etc. so in present study. We try to prove our hypothesis with data collected and analysed on the basis of patient taken in OPD and IPD level as open level randomized clinical trial. The material method, Analysis of data, Result and Conclusion is elaborated in the following Article.